Disability in people affected by leprosy: the role of impairment, activity, social participation, stigma and discrimination - van Brakel, Wim H.; Sihombing, Benyamin; Djarir, Hernani; Beise, Kerstin; Kusumawardhani, Laksmi; Yulihane, Rita; Kurniasari, Indra; Kasim, Muhammad; Kesumaningsih, Kadek I.; Wilder-Smith, Annelies (Global health action, 2012)
Background : Leprosy-related disability is a challenge to public health, and social and rehabilitation services in endemic countries. Disability is more than a mere physical dysfunction, and includes activity limitations, stigma, discrimination, and social participation restrictions. We assessed the extent of disability and its determinants among persons with leprosy-related disabilities after release from multi drug treatment. Methods : We conducted a survey on disability among persons affected by leprosy in Indonesia, using a Rapid Disability Appraisal toolkit based on the International Classification of Functioning, Disability and Health. The toolkit included the Screening of Activity Limitation and Safety Awareness (SALSA) scale, Participation Scale, Jacoby Stigma Scale (anticipated stigma), Explanatory Model Interview Catalogue (EMIC) stigma scale and Discrimination assessment. Community members were interviewed using a community version of the stigma scale. Multivariate linear regression was done to identify factors associated with social participation. Results : Overall 1,358 persons with leprosy-related disability (PLD) and 931 community members were included. Seventy-seven percent of PLD had physical impairments. Impairment status deteriorated significantly after release from treatment (from 59% to 77%). Around 60% of people reported activity limitations and participation restrictions and 36% anticipated stigma. As for participation restrictions and stigma, shame, problems related to marriage and difficulties in employment were the most frequently reported problems. Major determinants of participation were severity of impairment and level of education, activity and stigma. Reported severity of community stigma correlated with severity of participation restrictions in the same districts. Discussion : The majority of respondents reported problems in all components of disability. The reported physical impairment after release from treatment justifies ongoing monitoring to facilitate early prevention. Stigma was a major determinant of social participation, and therefore disability. Stigma reduction activities and socio-economic rehabilitation are urgently needed in addition to strategies to reduce the development of further physical impairment after release from treatment.